Pelatihan Dan Pendampingan Digital Marketing Sebagai Upaya Peningkatan Omset Pada Ud. Matahari Desa Kertasada Kec.Kalianget Kab.Sumenep - Dewi Wulansari; Silvia Agustina; Siti Nasihatul Magfiroh; Intan Permata Sari; Saifuddin Saifuddin; Moh. Hamdani Indra Saputra; Renaldy Nur Hidayatullah; Nur Diana Khalida Sukma (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The digital world currently has a very beneficial impact, including in the business world. The application of digital marketing in the business world opens up communication between potential consumers and sellers which can now be done without distance and time limitations. However, in this digital era, it turns out that there are still business actors who have not utilized digital marketing. Some still market their products conventionally so their market share is still limited. This results in sales income tending to remain constant. This internship program aims to increase the awareness and skills of UD. Matahari produces amplang crackers in Kertasada Village, District. Kalianget District. Sumenep regarding the importance of digital marketing to increase sales income with training and mentoring methods. Through this internship program, it is hoped that the market share will increase, so it has the potential to increase sales income.